Green synthesis and characterization of RGO/Cu nanocomposites as photocatalytic degradation of organic pollutants in waste-water. (17th June 2021) - Safajou, Hamed; Ghanbari, Mojgan; Amiri, Omid; Khojasteh, Hossein; Namvar, Farzad; Zinatloo-Ajabshir, Sahar; Salavati-Niasari, Masoud
Abstract: Recently, nanocomposite photocatalysts based on semiconductors have attracted much attention due to their suitable bandgap. Combination of tow of several semiconductors can slow down the electron-hole recombination. In this regard, we have depicted an eco-friendly and green fabrication technique to synthesize RGO/Cu nanocomposite by the reduction of graphene oxide and Cu 2+ ion utilizing spearmint extract as a reductant and capping agent. The sample was identified by FTIR, XRD, FESEM, EDS, HRTEM, and CV. The results of photocatalytic performance revealed that RGO/Cu is an efficient catalyst for degrading organic pollutants. This compound can eliminate Rhodamine B (RhB) and Methylene blue (MB) 91.0% and 72.0%, respectively. Highlights: A scalable, facile, cost-effective, and eco-friendly technique was used to fabricate rGO/Cu nanocomposites. Spearmint extract was used as a reducing and capping agent to reduce GO and Cu 2+ ion. Study of photocatalytic behavior of rGO/Cu nanocomposite.